Production of solid biomass and investigation of optimum thermal properties - Karsli, S.; Sarac, H. (TAYLOR & FRANCIS INC, 2018)
Recognizing the fact that 5% of annual global primary production of biomass should cover 50% of the world's current primary energy demand, plants widely available in Turkey, such as Astragalus, great mullein and sunflower, have been pelletized mixed in specific amounts to investigate their burning behaviors versus other fuels. Taguchi method was used to obtain a pelletized fuel with maximum calorie, low humidity, and low ash. Results suggested that the pellet has low humidity and ash content, while its caloric value is greater than that of the pomace, lignite, wood, sawdust, or animal and plant wastes used as fuel.
Keywords: Briquette; great mullein; pellets; renewable energy; solid biomass; sunflower; wild liquorice; TURKEY; Energy & Fuels; Engineering; Environmental Sciences & Ecology